Pemanfaatan Teknologi Informasi dalam Menunjang Profesionalitas Guru SDN 012 Balikpapan Utara - Dwi Arief Prambudi; Nia Febrianti; Eko Subastian (Perkumpulan Kualitama Edukatika Indonesia, 2022)
Advances in technology and science in the current era of globalization, especially in the field of computers. The ability to operate a computer is needed in various fields of work. This ability is not only familiar with computers globally, but also an elementary school teacher is required to be able to operate a computer as a learning medium and one way to complete the work that will be presented to students as well as efforts to increase knowledge competence in the field of computers, in accordance with the Government's target which aims to developing ICT programs and helping digital generations who are not technologically savvy. The design of training materials is expected to improve some of the teacher's abilities, including being able to make reports on student learning outcomes using Microsoft Word, Microsoft Excel and Power Point. Participants in this training were 20 teachers at SDN 012 North Balikpapan.